1994
DOI: 10.1104/pp.106.3.1195
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Defense-Related Proteins in Transformed Root Cultures of Trichosanthes kirilowii Maxim. var japonicum (Kitam.)

Abstract: We have established transformed ("hairy") root cultures from Trichosanthes kirilowii Maxim. var japonicum Kitam. (Cucurbitaceae) and four related species to study the biosynthesis of the ribosome-inactivating protein trichosanthin (TCN) and other rootspecific defense-related plant proteins. Stable, fast-growing root clones were obtained for each species by infecting in vitro grown plantlets with Agrobacferium rhizogenes American Type Culture Collection strain 15834. Each species accumulated reproducibly a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…The major protein in the basic protein fraction was tentatively identified as a class III chitinase based on the N-terminal amino acid sequence. This is consistent with the report by Savary and Flores [14], who identified two major extracellular basic proteins and one intracellular basic protein produced by T kirilowii var. japonica hairy roots as class III chitinases.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The major protein in the basic protein fraction was tentatively identified as a class III chitinase based on the N-terminal amino acid sequence. This is consistent with the report by Savary and Flores [14], who identified two major extracellular basic proteins and one intracellular basic protein produced by T kirilowii var. japonica hairy roots as class III chitinases.…”
Section: Discussionsupporting
confidence: 82%
“…However, the N-terminal sequence of HR-PB 1 was very similar to but not identical with the sequence of any of these proteins. The present result, together with the report describing very low level production of trichosanthin in the hairy roots [14] and transformed callus tissues [15], suggests that production of karasurin or trichosanthin may be associated with induction of secondary growth of roots. Chemical treatments, including addition of sucrose or jasmonates, have been shown to induce accumulation of sporamine in the leaf-petiole region of sweet potatoes [16] and expression of vegetative storage protein genes in soybean [17].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…A. rhizogenes-transformed hairy roots, in general, exhibit morphological and genetic similarity with fibrous primary roots (for review, see Vivanco and Flores, 2000;Bais et al, 2001). Savary and Flores (1994) have shown that secondary growth induction leading to storage root formation shifts the protein production and accumulation patterns of RIPs. Therefore, PAP-H may be considered a biochemically identical isoform to the protein found in the primary roots.…”
Section: Discussionmentioning
confidence: 99%
“…Hairy roots show stable expression of root-specific biosynthetic pathways, and thus have been used as an experimental system to study the biology and biochemistry of underground organs (Flores and Curtis, 1992;Flores et al, 1999). Plant roots synthesize and store various macromolecules, including storage and defense-related proteins such as chitinase and ␤-1,3-glucanase, to cope with pathogenic challenge (Mauch et al, 1988;Linthorst, 1991;Savary and Flores, 1994;Savary et al, 1997). Here, we report the identification of a novel RIP, termed PAP-H, located in the cell walls of hairy roots and root border cells of pokeweed.…”
mentioning
confidence: 99%